Business Development Strategy of Nii Kutchen Bakery Bengkalis Using Business Model Canvas and SWOT Analysis - Feby Sisca; Hutomo Atman Maulana (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2023)
This study aims to design a strategy for developing a Bakery business using the Business Model Canvas and SWOT Analysis approach at Nii Kutchen Bakery Bengkalis. The type of research used by the author is descriptive qualitative with the aim of designing new strategies that are used to maintain business and develop businesses that are increasingly competitive. Data collection techniques in this study were interviews, observation and documentation. The object of this research is Nii Kutchen Bakery Bengkalis. The results of the study show that the results of the Business Model Canvas at Nii Kutchen Bakery Bengkalis indicate the need for a new strategy change because there are still many segments that cannot compete with competitors. So it can be concluded that it is necessary to design a new strategy through SWOT Analysis on each element of the Business Model Canvas to be implemented by Nii Kutchen Bakery Bengkalis in the future.